Human Health Risk Assessment of Heavy Metals and Metalloids in Herbal Medicines Used to Treat Anxiety: Monitoring of Safety - Geronimo, Ana C. R.; Melo, Elaine S. P.; Silva, Kassia R. N.; Pereira, Hugo S.; Nascimento, Valdir A.; Machate, David J.; do Nascimento, Valter A. (Frontiers in Pharmacology, 2021)
The present study estimated the human health risk assessment and daily intake of heavy metals and metalloids in herbal medicines used to treat anxiety in Brazil. Six different brands of herbal medicines were purchased in the city of Campo Grande/MS, Brazil: Pasalix®, Calman®, Serenus®, Maracugina®, Prakalmar® and Calmasyn®. In total, eight elements including As, Ba, Cd, Co, Cr, Cu, Fe, and Pb were analyzed using optical emission spectrometry with induc-tively coupled plasma (ICP OES). Only the concentration of As in the herbal medicine Prakalmar® is above the values established by United States Pharmacopoeia Convention (USP) and Brazilian Pharmacopoeia (BF) for permitted con-centration of elemental impurities in drugs substances. The concentration of Ba, Cd, Co, Cr and Cu in all herbal medi-cines are lower than the values set by USP and FB. The concentration of Pb in Calman® is lower than the limits estab-lished by BF, but higher than those established by USP. Pasalix, Serenus®, Calmasyn®, Prakalmar® and Marcacugina® have a higher Pb concentration than the values allowed by USP and BF. All herbal medications have concentrations within safe ranges for human consumption, with the exception of Calmasyn®, which has Pb over the value defined by USP for oral permissible daily exposure (PDE) for elemental impurities. The values of estimated daily intake (EDI) of metal(loid)s in adults and children obtained from the consumption of the herbal medicines are below the values stipu-lated by the minimal risk levels (MRLs). All the hazard index (HI) values recorded in this study were below 1. However, monitoring by regulatory agency is necessary, large doses of heavy metal may cause acute or chronic toxicities.